Research on Hydraulic Fracturing Pressure Relief Technology in the Deep High-Stress Roadway for Surrounding Rock Control - Wen Zhai; Yachao Guo; Xiaochuan Ma; Nailv Li; Peng Zhang; Kun Ma; Yuanxin Jing; Hong Yu; Xiaotong Li (Advances in Civil Engineering)
With the increase of mining depth in underground engineering, deep ground pressure has an extremely unfavorable impact on safety production and the economic benefits of coal mines and the control of the roadway stability in deep mines are gradually highlighted. In this study, the working face 14203 of the Zaoquan coal mine was taken as the engineering background, the deformation mechanism of surrounding rock in the deep-buried high-stress roadway was analyzed, and the hydraulic fracturing pressure relief technology in the advanced roadway was proposed for surrounding rock control. Finally, the numerical simulation and field tests were used to validate the comprehensive effect of the proposed technology. Without damaging the roadway stability in the working face, the hydraulic fracturing pressure relief technology can optimize the stress environment and stability of the roadway through the artificial control of the roof fracture position. The numerical simulation shows that under the action of hydraulic fracturing, the cutting slot is formed, the deformation and failure mode of the roof are changed, the stress of surrounding rock is reduced, and the development of the plastic zone of surrounding rock is limited. As a result, the stability of surrounding rock in the roadway is effectively protected. The field test shows that after the adoption of hydraulic fracturing pressure relief technology, the roof subsidence, floor separation, bolt stress, and cable stress decrease, and the deformation of surrounding rock is reduced significantly. Therefore, hydraulic fracturing pressure relief technology is verified as an effective method to control the large deformation of the surrounding rock in the deep-buried roadway.